ASIDES İN TURKISH POLITICAL NEWSPAPER INTERVIEWS - ESMER, Elçin (International Journal of Research -GRANTHAALAYAH, 2021)
The newspaper genre is generally accepted as one of the most important examples of the persuasive text genre. ‘Asides’ are the short dialogues inserted by journalists to give their personal comments on the subject being reported. They therefore play a crucial role for journalists to persuade their readers and interact with them. Interviews are one of the characteristic features of newspaper discourse. This study examines the usage of asides in political interviews conducted with prominent politicians in Turkey. The data consisted of seventy political interviews published in six elite mainstream newspapers which had different ideologies, three pro-government and three anti-government. In line with the aim of the study, the research uses a descriptive survey design. Quantitative and qualitative methods are applied using the methodologies of both Corpus Linguistics and Critical Discourse Analysis. The asides in the interviews are identified using Temmerman’s (2013, 370-371) classification of asides and Hyland’s (2005, 49) taxonomy. Also, the corpus is analysed using the NooJ linguistic engine module. The results show that there are variations in the use and distribution of asides in the data according to the politicians’ and the newspapers’ ideologies.